Resolving phylogenetic conflicts in Pandanales: the dual roles of gene flow and whole-genome duplication - Shi, Tian; He, Jian (Frontiers in Plant Science, 2025)
IntroductionAccurate phylogenetic reconstruction is crucial for understanding evolutionary relationships and biodiversity. Despite advances in molecular systematics, the relationships within Pandanales—which include Cyclanthaceae, Pandanaceae, Stemonaceae, Triuridaceae, and Velloziaceae—remain unresolved. This study aims to clarify these relationships by analyzing transcriptomic and genomic data from these families.MethodsWe analyzed transcriptomic and genomic data from 20 samples representing all five families of Pandanales. Our approach involved assembling 2,668 single-copy orthologous genes (SCOGs) and conducting phylogenetic analyses using both coalescent- and concatenation-based methods, alongside plastid genome data. Additionally, we employed HyDe for gene flow analysis and conducted coalescent simulations and QuIBL analyses to explore sources of phylogenetic conflict. We also investigated whole-genome duplication (WGD) events within Pandanales.ResultsThe phylogenetic analyses produced strongly supported but topologically incongruent trees. Our gene flow analysis suggested that the concatenation-based topology likely reflects the true evolutionary history of Pandanales. We identified two significant ancient gene flow events: one between Velloziaceae and Triuridaceae, and another between Triuridaceae and the C-P clade (Cyclanthaceae + Pandanaceae). Furthermore, we detected five whole-genome duplication (WGD) events, including two that occurred before the Cretaceous–Paleogene boundary in Stemonaceae and Pandanaceae, one in Triuridaceae during the mid-Paleogene, and two within Velloziaceae near the Paleogene–Neogene boundary.DiscussionOur findings indicate that gene flow, rather than incomplete lineage sorting, is the primary source of phylogenetic conflict at certain nodes within Pandanales. The identified WGD events likely played a significant role in facilitating adaptation and diversification under changing environmental conditions. These results not only resolve long-standing phylogenetic conflicts but also enhance our understanding of the mechanisms driving plant diversification within this order.